2023
DOI: 10.7759/cureus.35525
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Recurrence Risk of Chronic Subdural Hematoma After Surgical Drainage

Abstract: IntroductionChronic subdural hematoma (CSDH) is one of the most encountered neurosurgical cases. CSDH is defined as the accumulation of liquified blood products in the space between the dura and the arachnoid. A reported incidence of 17.6/100,000/year has more than doubled in the past 25 years in parallel with an aging population. Surgical drainage remains the mainstay of treatment, yet it is challenged by variable recurrence risks. Less invasive embolization methods of the middle meningeal artery (EMMA) could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the rate of perioperative complications and mortality observed in CSDH cohorts varies from 0% to 32%. These complications are not always caused by the surgical procedure itself but are secondary to other factors such as preexisting active medical conditions and frailty 18,19 . MMA embolization, which is typically done endovascularly, is well tolerated and is also considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of perioperative complications and mortality observed in CSDH cohorts varies from 0% to 32%. These complications are not always caused by the surgical procedure itself but are secondary to other factors such as preexisting active medical conditions and frailty 18,19 . MMA embolization, which is typically done endovascularly, is well tolerated and is also considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization of MMA is a new management option that lacks supporting evidence over surgical management; however, it is a safe option when used in conjunction with surgical management to decrease the recurrence rate [ 5 , 14 ]. Even so, it has some complications; treatment failure is the most common one, which can result in worsening of the hematoma and neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that using a drainage tube significantly reduces recurrence rates compared to treatments without it [ 8 ]. A retrospective cohort study of 102 patients with cSDH showed that the risk of mortality and recurrence was 14.5% and 32% for patients undergoing craniotomy compared to only 8.7% and 17.7% of patients receiving burr hole drainage treatment, respectively [ 8 ]. Despite the presence of various drainage methods, subdural drainage remains prevalent.…”
Section: Introductionmentioning
confidence: 99%